A coupled chemo-elastic cohesive zone model for backfill-rock interface. (September 2020) - Fang, Kun; Cui, Liang; Fall, Mamadou
Abstract: To date, only a very few number of models are available to study the shear characteristics of the backfill-rock interface, and none of them have incorporated the effect of the interactions between sulphate ions and cement hydration on the interface shear behaviour. Therefore, a coupled chemo-elastic cohesive zone model (CZM) has been developed to simulate the shear characteristics of the cemented paste backfill (CPB)-rock interface that contains sulphate ions at the early ages. To quantitatively address the influence of sulphate on binder hydration at the early ages, the concept of equivalent chemical age is proposed and integrated into a binder hydration model. Besides, the interface shear properties, fracture toughness as well as shear stiffness are expressed as a function of the equivalent chemical age. By implementing the developed model in COMSOL Multiphysics, the results of the numerical simulation are found to agree with the experimental results. The validated results confirm the capability of the developed model to describe the shear characteristics of the interface that contains sulphate ions. The developed model will contribute to improving the assessment of the shear behaviour of the CPB-rock interface in the field, thus leading to a more economical design of safe CPB structures.